To find the product of the polynomials \( (2x + 1)(x - 4) \), we will use the distributive property (also known as the FOIL method for binomials).
Here are the steps:
-
Distribute \( 2x \) to both \( (x - 4) \): \[ 2x \cdot x = 2x^2 \] \[ 2x \cdot (-4) = -8x \]
-
Distribute \( 1 \) to both \( (x - 4) \): \[ 1 \cdot x = x \] \[ 1 \cdot (-4) = -4 \]
Now, combine all the results: \[ 2x^2 - 8x + x - 4 \]
Combine like terms (\(-8x + x\)): \[ 2x^2 - 7x - 4 \]
Thus, the product of the polynomials \( (2x + 1)(x - 4) \) is: \[ \boxed{2x^2 - 7x - 4} \]